2013
DOI: 10.1080/01635581.2014.851715
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between 25-Hydroxyvitamin D and Mammographic Density in Healthy Pre- and Postmenopausal Women Regardless of the Menstrual Cycle Phase: A Cross-sectional Study

Abstract: Vitamin D deficiency is a known risk factor of breast cancer. An association between vitamin D and breast density has been suggested; however, it remains controversial. The aim of this study was to determine the association between serum 25-hydroxyvitamin D [25(OH)D] level and mammographic density. Subjects in our study included 517 patients who visited the health promotion center of the University Hospital. Mammographic density was classified using the American College of Radiology, Breast Imaging Reporting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…Our finding of non-significant association overall between serum 25(OH)D3 levels and MD among premenopausal women is consistent with results from several studies [2123, 25]. More recently the study by Crew et al on 195 women aged 40–60 years found no association between serum 25(OH)D and different measures of MD, however [22].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding of non-significant association overall between serum 25(OH)D3 levels and MD among premenopausal women is consistent with results from several studies [2123, 25]. More recently the study by Crew et al on 195 women aged 40–60 years found no association between serum 25(OH)D and different measures of MD, however [22].…”
Section: Discussionsupporting
confidence: 91%
“…More recently the study by Crew et al on 195 women aged 40–60 years found no association between serum 25(OH)D and different measures of MD, however [22]. In a recent Korean study, the authors reported a small but statistically significant association between serum 25(OH)D and MD in correlation analyses, but no significant association was observed in the multivariable regression analyses [23]. A cross-sectional study by Chai et al, showed that serum 25(OH)D was not associated with MD among 182 premenopausal women [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of eight previous investigations of 25(OH)D and mammographic density (2027), five of which included premenopausal women (20, 21, 24, 25, 27), none reported evidence of a statistically significant association overall. However, two prior studies reported inverse associations between seasonal changes in plasma 25(OH)D and mammographic density (21, 27).…”
Section: Discussionmentioning
confidence: 91%
“…Because vitamin D has anti-proliferative and pro-differentiation effects in normal breast tissue (19) and therefore could have direct or indirect influences on breast tissue composition, we hypothesized that women with higher plasma 25(OH)D would have lower percent mammographic density. Prior investigations of this hypothesis have mostly reported null findings (2028); however, these studies have been limited by fairly small sample sizes and few have included premenopausal women (20, 21, 24, 25). Understanding how vitamin D may influence mammographic density among premenopausal women may enhance our understanding of breast cancer etiology.…”
Section: Introductionmentioning
confidence: 99%